Direct synthesis of primary amines via ruthenium-catalysed amination of ketones with ammonia and hydrogen - Gallardo-Donaire, Joan; Ernst, Martin; Trapp, Oliver; Schaub, Thomas (Advanced synthesis & catalysis, 2016)
A highly selective reductive amination of ketones to primary amines with ammonia and hydrogen using a simple ruthenium catalyst has been developed. The protocol described constitutes an efficient and direct atom-economical approach en route to α-methylbenzylamine derivatives in good to high yields. The presence of catalytic amounts of aluminum triflate turned out to be crucial for achieving high conversion towards primary amines.
Gesehen am 06.05.2020